Decline in Relative Abundance of Bottlenose Dolphins Exposed to Long‐Term Disturbance - LARS BEJDER; AMY SAMUELS; HAL WHITEHEAD; NICK GALES; JANET MANN; RICHARD CONNOR; MIKE HEITHAUS; JANA WATSON‐CAPPS; CINDY FLAHERTY; MICHAEL KRÜTZEN (Conservation Biology, 2006)
Studies evaluating effects of human activity on wildlife typically emphasize short‐term behavioral responses from which it is difficult to infer biological significance or formulate plans to mitigate harmful impacts. Based on decades of detailed behavioral records, we evaluated long‐term impacts of vessel activity on bottlenose dolphins ( Tursiops sp.) in Shark Bay, Australia. We compared dolphin abundance within adjacent 36‐km 2 tourism and control sites, over three consecutive 4.5‐year periods wherein research activity was relatively constant but tourism levels increased from zero, to one, to two dolphin‐watching operators. A nonlinear logistic model demonstrated that there was no difference in dolphin abundance between periods with no tourism and periods in which one operator offered tours. As the number of tour operators increased to two, there was a significant average decline in dolphin abundance (14.9%; 95% CI =−20.8 to −8.23), approximating a decline of one per seven individuals. Concurrently, within the control site, the average increase in dolphin abundance was not significant (8.5%; 95% CI =−4.0 to +16.7). Given the substantially greater presence and proximity of tour vessels to dolphins relative to research vessels, tour‐vessel activity contributed more to declining dolphin numbers within the tourism site than research vessels. Although this trend may not jeopardize the large, genetically diverse dolphin population of Shark Bay, the decline is unlikely to be sustainable for local dolphin tourism. A similar decline would be devastating for small, closed, resident, or endangered cetacean populations. The substantial effect of tour vessels on dolphin abundance in a region of low‐level tourism calls into question the presumption that dolphin‐watching tourism is benign.